"[P]lain and passive fortitude": Stoicism and Spaces of Dissent in Sejanus. Issue 1 (May 2018) - Smith, M. Burdick
Abstract : In Ben Jonson's Sejanus, performed at court in the first year of King James' reign in 1603, Arruntius seemingly figures as "Jonson's spokesperson." While lauding the moral responsibility of Arruntius, some critics have portrayed the Senator as a passive Stoic whose "only outlet is speech." For a poet who emphasizes the moral and didactic responsibility of authorship, why, then, does his spokesman inhabit a peripheral space in criticism? Critical interpretation of Arruntius depends on the editorial decision to render many of Arruntius' lines as asides or as public critique, and this editorial crux is examined vis-à-vis early modern attitudes toward public engagement. I argue that the play negotiates the tensions between the patient Neostoicism of Justus Lipsius and politically active Senecan Stoicism. Arruntius navigates those tensions through Ciceronian ideals of friendship, which provide an alternative to the rampant flattery and tyranny at Tiberius' court. I show that the play responds to larger political anxieties concerning James I's recent ascension to the throne, and that interpreting early modern Stoicism as entirely passive disregards the complex discourse of friendship that permeates the period.